If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = 2(pi)(r) Multiply ip * r 12 = 2ipr Solving 12 = 2ipr Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-2ipr' to each side of the equation. 12 + -2ipr = 2ipr + -2ipr Combine like terms: 2ipr + -2ipr = 0 12 + -2ipr = 0 Add '-12' to each side of the equation. 12 + -12 + -2ipr = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -2ipr = 0 + -12 -2ipr = 0 + -12 Combine like terms: 0 + -12 = -12 -2ipr = -12 Divide each side by '-2pr'. i = 6p-1r-1 Simplifying i = 6p-1r-1
| 7y-2-y+8= | | 1.1(-4g-2)-0.2g= | | -2(3p+5)-3(4p-8)= | | -7x+3x+15-9x= | | 6.9x-4+3x-1.8= | | 2y+1.5-4.3y+1.8y+1= | | (4x^2-9)(x^2-10)=0 | | 6/5y-2/5=-4y-1/3 | | -5(6n+1)=55 | | 11y/y | | 2x(3)=5x-4/3 | | 4x^3+4x^2=7x | | 25m^2-16/49 | | 7.48n+3.77=-3.22n+6.21 | | 8.08n+2.43=-3.13n+4.86 | | 8.08n+2.43=3.13n+4.90 | | 8.10n+2.45=-3.15n+4.85 | | 8.08n+2.43=3.13n+4.86 | | 7x-9=-38 | | (3x+1)2=5 | | log(6x+4)=1+log(x-5) | | -6r+250=-100+0.2(y-0.25y)+0.25y | | -6r+250=-100+0.2(y-0.25y) | | 8x-8=-9 | | r^2-12r-1=0 | | -[3z^2+4z-(2z^2-8z)]+[(9z^2-[5z-z^2])+5z^2]= | | -30=-6(3n-7) | | -30=6(3n-7) | | -8x+y-x+7y= | | .03x^2-9x+600=0 | | -(8-r)=-15 | | x^2+x+0.25=25 |